2017
DOI: 10.1007/s11064-017-2250-8
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Improves Water Maze Learning and Memory Performance While Reduces Hyperphosphorylation of Tau and Neurofilaments in APP/PS1/Tau Triple Transgenic Mice

Abstract: The purpose of this study was to explore how liraglutide affects AD-like pathology and cognitive function in APP/PS1/Tau triple transgenic (3 × Tg) Alzheimer disease (AD) model mice. Male 3 × Tg mice and C57BL/6 J mice were treated for 8 weeks with liraglutide (300 μg/kg/day, subcutaneous injection) or saline. Levels of phosphorylated tau, neurofilaments (NFs), extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK) in brain tissues were assessed with western blots. Fluoro-Jade-B labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 39 publications
2
44
1
Order By: Relevance
“…Data are presented as mean ± SEM. *P < 0.05; **P < 0.01. n = 6/group Cognitive deficits are the main manifestation of AD [34]. In the present study, the data showed that 27-OHC effectively aggravated cognitive deficits in the APP/PS1 mice as shown by the Morris water maze test and the passive avoidance test.…”
Section: Discussionsupporting
confidence: 58%
“…Data are presented as mean ± SEM. *P < 0.05; **P < 0.01. n = 6/group Cognitive deficits are the main manifestation of AD [34]. In the present study, the data showed that 27-OHC effectively aggravated cognitive deficits in the APP/PS1 mice as shown by the Morris water maze test and the passive avoidance test.…”
Section: Discussionsupporting
confidence: 58%
“…No other changes in neurocognition were observed in our study. Liraglutide improves spatial memory in rodent models of Alzheimer's disease, but we may not have observed similar changes because of our healthy study population.…”
Section: Discussionmentioning
confidence: 85%
“…Recent evidence suggests hyperphosphorylation of neurofilaments (Chen et al, 2017 ) and decreased MAP-2 levels (Soares et al, 2016 ) in the hippocampus are correlated with cognitive and anxiety dysfunctions in murine models of neurodegeneration and global cerebral ischemia, respectively. In the present study, PA-induced hippocampal accumulation of pNF-H/M and reduction of MAP-2 at P30 exhibited a similar behavioral correlate.…”
Section: Discussionmentioning
confidence: 99%